Industrial Class Model during the Pandemic to Support Link and Match Industries and Vocational High Schools - Khirdany, Elvin Nury; Widiyanti, Widiyanti; Yoto, Yoto (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
The industrial class was formed to provide a knowledge and broader insight to students based on the development of competencies required by industries. However, several Vocational High Schools (VHS) unused industrial classes during the pandemic because the school partner industries is being impacted by the Covid-19 pandemic. The study was conducted to determine the implementation of industrial class model used during the pandemic. The research method uses quasi-qualitative. The research was conducted at Telkom Malang Vocational High School on software engineering skills competency. The finding showed collaboration form in the industrial class between industriesand VHS are curriculum synchronization, student selection, teacher training, implementation of street vendors and job recruitment. The implementation of industrial class is done online by monitoring students by school and industry supervisors. Industrial class students have a group project task formed. Supporting and inhibiting factors in the sustainability of the industrial class during the pandemic. Supporting factors are selected students with high abilities by selection process, and industrial partner support for industrial class implementation. While the inhibiting factor is online learning process, it cannot help the teacher to monitor student activities and build students mental directly. The industrial class was formed to provide a knowledge and broader insight to students based on the development of competencies required by industries. However, several Vocational High Schools (VHS) unused industrial classes during the pandemic because the school partner industries is being impacted by the Covid-19 pandemic. The study was conducted to determine the implementation of industrial class model used during the pandemic. The research method uses quasi-qualitative. The research was conducted at Telkom Malang Vocational High School on software engineering skills competency. The finding showed collaboration form in the industrial class between industriesand VHS are curriculum synchronization, student selection, teacher training, implementation of street vendors and job recruitment. The implementation of industrial class is done online by monitoring students by school and industry supervisors. Industrial class students have a group project task formed. Supporting and inhibiting factors in the sustainability of the industrial class during the pandemic. Supporting factors are selected students with high abilities by selection process, and industrial partner support for industrial class implementation. While the inhibiting factor is online learning process, it cannot help the teacher to monitor student activities and build students mental directly.